PERANAN SISTEM INFORMASI MANAJEMEN DALAM BIDANG PENDIDIKAN PADA SAAT COVID-19: Systematic Literature Review - Alvin Hendrawan (Shofanah Media Berkah, 2023)
Management Information Systems (MIS) in the field of education is a concept that utilizes information and communication technology to increase efficiency, effectiveness and transparency in the management of the educational process. In the context of education, MIS helps manage various aspects related to the management of educational institutions, from student and staff administration, curriculum and scheduling, to performance monitoring and evaluation. The purpose of using MIS in the education sector is to facilitate and improve the quality of decision-making by education stakeholders, such as school principals, lecturers, teachers and administrative staff. Through SIM, data and information related to education can be collected, stored, managed and accessed more efficiently. MIS also helps improve communication and collaboration between various parties involved in the educational process, including students, parents and other educational institutions.